Development of hypotension in patients newly diagnosed with heart failure in UK general practice: retrospective cohort and nested case–control analyses. Issue 7 (11th July 2019) - Martín-Pérez, Mar; Michel, Alexander; Ma, Mark; García Rodríguez, Luis Alberto
Abstract : Objectives: Hypotension is of particular relevance for patients with heart failure (HF), since almost all HF drugs cause lowering of blood pressure (BP) and it is associated with a poor prognosis. We aimed to investigate hypotension incidence and risk factors in patients with incident HF in the UK. Design: Retrospective cohort study including nested case–control analyses. Setting: The Health Improvement Network UK primary care database. Participants: 18 677 adult patients with incident HF during 2000–2005 were followed and cases of hypotension (systolic BP ≤90 mm Hg) were identified. Controls were age-matched, sex-matched and date-matched to cases (1:2). Primary and secondary outcome measures: We estimated hypotension incidence in the full study population and relevant subgroups (eg, sex and age). Potential risk factors for hypotension overall and for multiple versus single hypotensive episodes were evaluated using conditional logistic regression and unconditional regression models, respectively. Results: During a mean follow-up of 3.31 years, 2565 patients (13.7%) developed hypotension. The incidence of hypotension was 3.17 cases per 100 patient years (95% confidence interval (CI): 3.05–3.30), and was markedly increased in women aged 18–39 years (n=32; 17.72 cases per 100 patient-years; 95% CI: 9.69–29.73). Hypotension risk factors included high healthcare utilisation (proxy measure for HF severity and general comorbidity; eg, ≥10 primary care physician visits versus none, odds ratio (OR): 2.29; 95% CI: 1.34–3.90), previous hypotensive episodes (OR: 2.32; 95% CI: 1.84–2.92), renal failure and use of aldosterone antagonists, angiotensin-converting enzyme inhibitors and angiotensin receptor blockers. Risk factors identified for hypotension generally overlapped with those for multiple versus single hypotensive episodes. Conclusions: Hypotension occurs frequently in patients with incident HF. Our findings may help identify patients most likely to benefit from close BP monitoring. The increased incidence of hypotension in young women with HF requires investigation.